Joint treatment of landfill leachate with municipal wastewater by submerged membrane bioreactor - Hasar, Halil; Ipek, Ubeyde; Kinaci, Cumali (I W A Publishing, 2009)
Young leachate was a high strength wastewater with regard to carbon and nitrogen matter, and up to now many researchers have focused on a number of treatment methods to treat the leachate. By using various treatment processes, joint treatment of leachate with domestic wastewater, resulted from same community, is one of the most significant methods because domestic wastewater has either larger mass or lower strength than leachate. In this study, a submerged membrane bioreactor (sMBR) was used for treatment of blending wastewater, including differential mixture ratios of domestic wastewater and leachate. In raw leachate, BOD(5)/COD was between 0.40 and 0.67 and total phosphorus was between 17 and 24 mg/l. After the leachate was blended with domestic wastewater in the ratios of 1/5-1/20, the influent COD decreased from 8,500-14,200 mg/l to 750-2,400 mg/l as ammonium decreased from 1,100-2,150 mg/l to 30-180 mg/l. The sMBR, which was aerated intermittently, accomplished both COD oxidation and nutrient removal at optimal conditions without adding the external phosphorus source, providing < 15mg COD/l, < 1.3 mg NH(4)(+)-N/l, and < 2.0 mg P/l on average at solid retention times (SRT) higher than 10 days. Consequently, the results showed the mixture of leachate and domestic wastewater could be an acceptable alternative by means of membrane bioreactor technology.
Keywords: domestic wastewater; joint treatment; leachate; membrane bioreactor